Rare complication spontaneous pneumothorax and pneumomediastinum in COVID-19 patients: A single center experience - Tüzün, Türkan; Ekinci, Yasin (The Journal of Infection in Developing Countries, 2023)
Introduction: We aimed to describe the clinical characteristics and outcomes of patients with spontaneous pneumothorax (SPT) and pneumomediastinum (SPM) due to COVID-19 pneumonia. Methodology: This retrospective study evaluated inpatients at a COVID-19 pandemic hospital. Between March 11, 2020 and March 31, 2021, patients who developed complications of spontaneous pneumothorax (SPT) and pneumomediastinum (SPM) with a confirmed diagnosis of SARS-CoV-2 by polymerase chain reaction (PCR) method were included. Results: Of the 6,528 hospitalized patients, nine developed complications of SPT and SPM, with an incidence of 0.14%. Four of these patients developed SPT, one developed SPM, one developed SPT + SPM + emphysema, and three developed SPT + SPM. The mean age of the patients was 67.67 ± 13.41 years and the median was 68 (45-88) years. All patients were male. Six patients died, one of whom died of myocardial infarction from uncomplicated causes. Conclusions: Studies with more cases are needed to evaluate the causality between COVID-19 and pneumothorax (PT) and pneumomediastinum (PM). However, it should be kept in mind that PT and PM may lead to this clinic when sudden respiratory distress occurs in these patients and rapid diagnosis and treatment should be planned. As observed in this study, PT and PM are important factors in the development of mortality in COVID-19 patients.